Perception of parents and guardians on safe distance for children to travel to public areas - Mohamed Osman, Mariana; Abdullah, Muhammad Faris; Khalid, Najihan; Bachok, Syahriah; Rabe, Noor Suzilawati; Shuid, Syafiee; Ponrohono, Zakiah (Malaysian Institute of Planners, 2017)
Children safety is of utmost important. Children are susceptible to safety risk while traveling to public areas such as schools, parks and bus stops. Perception of parents and guardians on the safety of their children determines their decision whether or not to allow their children to travel to public areas and how. This study looks at the perception of parents and guardians on the safe distance for children to travel to public areas. 4,500 respondents were surveyed. It was found that parents and guardians perception of safe distance is heavily influenced by distance and children's age factors.